Prussian blue coupling with zinc oxide as a protective layer: an efficient cathode for high-rate sodium-ion batteries. Issue 4 (17th December 2018) - Qiao, Yun; Wei, Gangya; Cui, Jiabao; Zhang, Mingming; Cheng, Xiaoguang; He, Dandan; Li, Shuan; Liu, Yang
Abstract : Prussian blue coupled with zinc oxide has been synthesized via a facial heat treatment process. Abstract : Prussian blue coupled with zinc oxide has been synthesized via a facial heat treatment process. As a cathode for sodium ion batteries, the PB coupled with ZnO delivers an excellent rate performance, retaining 86.2 mA h g −1 at 10 A g −1 and a high reversible capacity of 89.9 mA h g −1 at 0.2 A g −1 after 500 cycles.